Strategies for the innovative development of single-industry towns of Karaganda region - Маimurunova, А.А.; Аryn, Е.М. (BUKETOV BUSINESS REVIEW, 2019)
In the article the issues of innovative modernization of singe-industry towns in Karaganda region are discussed. The socio-economic consequences of the formation and development of single-industry towns are also identified. The results of the implementation of programs for the development of single-industry towns of the Republic of Kazakhstan for 2012–2020 were evaluated. At the same time, in Kazakhstan, operational decisions are required in single-industry local structures. The consequences of the impact of crises and changes on the economic situation of single-industry towns and as a result of an analysis of the main socio-economic indicators of the development of Karaganda region for 2014–2017 have been determined, the necessity of the socio-economic development of the regional single-industry towns and raising of the standard of living of the population has been justified. In many single-industry towns of the region, the population has declined, as a result of a significant reduction in the population in the cities of Shakhty, Abay, Temirtau, Zhezkazgan, etc. As a result of the analysis, the insufficient implementation of programs for the development of single-industry towns and cities with high social problems was identified, the need to expand the competence and executive functions of local authorities to solve permanent economic problems was identified. In addition to the implementation of state programs, each single-industry city should develop its own development strategies, innovative development, taking into account the region’s resource potential, focused on the region’s competitiveness.